Trichoderma polysporum selectively inhibits white-nose syndrome fungal pathogen Pseudogymnoascus destructans amidst soil microbes - Singh, Amanpreet (Microbiome, 2018)
BACKGROUND: Pseudogymnoascus destructans (Pd), the causative fungal agent of white-nose syndrome (WNS), has led to the deaths of millions of hibernating bats in the United States of America (USA) and Canada. Efficient strategies are needed to decontaminate Pd from the bat hibernacula to interrupt the disease transmission cycle without affecting the native microbes. Previously, we discovered a novel Trichoderma polysporum (Tp) strain (WPM 39143), which inhibited the growth of Pd in autoclaved soil samples. In the present investigation, we used culture-based approaches to determine Tp-induced killing of native and enriched Pd in the natural soil of two bat hibernacula. We also assessed the impact of Tp treatment on native microbial communities by metagenomics. RESULTS: Our results demonstrated that Tp at the concentration of 10(5) conidia/g soil caused 100% killing of native Pd in culture within 5 weeks of incubation. A 10-fold higher concentration of Tp (10(6) conidia/g soil) killed an enriched Pd population (10(5) conidia/g soil). The 12,507 fungal operational taxonomic units (OTUs, dominated by Ascomycota and Basidiomycota) and 27,427 bacterial OTUs (dominated by Acidobacteria and Proteobacteria) comprised the native soil microbes of the two bat hibernacula. No significant differences in fungal and bacterial relative abundances were observed between untreated and Tp-treated soil (10(5) Tp conidia/g soil, p ≤ 0.05). CONCLUSIONS: Our results suggest that Tp-induced killing of Pd is highly specific, with minimal to no impact on the indigenous microbes present in the soil samples. These findings provide the scientific rationale for the field trials of Tp in the WNS-affected hibernacula for the effective decontamination of Pd and the control of WNS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40168-018-0512-6) contains supplementary material, which is available to authorized users.